Caracteres agronômicos e teor de óleo em canola em função de épocas de semeadura, adubação de cobertura no florescimento e dessecação em pré-colheita - Rosa, Willian Bosquette (2019)
Inserted in Rio Grande do Sul in the 1970s and in Paraná in 1980, canola (Brassica napus L. var. Oleifera) presents great ease of insertion in crop rotation systems, has high productive potential and has been prominent in the production of biodiesel and edible oil of high nutritional value. However, some challenges such as the definition of the best hybrids and sowing times, better utilization of the prolonged flowering period and adjustments in the uniformity of silage maturation still need to be overcome in order for the crop to reach levels explored by crops such as soybean and corn. In this context, the objective of this work was to evaluate the phenometric characters, agronomic performance and oil content in the canola crop from different experiments carried out in the Western region of Paraná. In the year 2017 two experiments were conducted, one in the municipality of Entre Rios do Oeste and another in Marechal Cândido Rondon. A randomized complete block design was used in the subdivision plots system, where the plots represented six sowing seasons (April 07 and 22, May 07 and May 22 and June 06 and June 21), and the five hybrid subplots (Hyola 50, Hyola 61, Hyola 433, Hyola 571 CL and Hyola 575 CL). In another study the application of different doses of potassium (0, 15, 30, 60, 120 kg ha-1) in two phenological stages of flowering (F1 and F2) was studied, and a fourth experiment addressed the desiccation with different herbicides (paraquat, diquat and ammonium glufosinate at a dose of 400 g ai ha-1, glyphosate at 1440 g ai ha-1 and saflufenac at 70 g ai ha-1) plus the control at four phenological stages of silage maturation (G2 G3, G4 and G5). Both experiments were carried out in 2016 and conducted in randomized blocks in a factorial system 5x2 and 6x4 respectively and the evaluations were done on the hybrid Hyola 433. Regardless of the hybrid, plantings between April 7 and 22, characterized the best times for the implantation of the hybrid. canola, both in Entre Rios do Oeste and in Marechal Cândido Rondon and later sowing, significantly reduce the duration of the phenometric variables and agronomic performance of the crop. In general, Hyola hybrids 50, 61 and 433 expressed the best results, considering the variables analyzed. Although it did not influence variables such as yield and oil content in the grains, regardless of the time of application the potassium doses increased the duration of flowering and the crop cycle, as well as the number of silicas per plant and the number of grains per silica. However, the study with desiccation in maturation showed that drying out the culture in the phenological stages G2 and G3 negatively affects all the analyzed variables, except for the advance of the cycle. However, under climatic adversities such as high winds, excessive rainfall or hail, effecting G4 desiccation with any of the herbicides may be a viable alternative to advance the removal of the grains from the field and avoid losses in the oil content. However, to preserve the maximum agronomic performance of the crop, desiccation in G5 is the most recommended.